An embedded barcode for "connected" malaria rapid diagnostic tests. Issue 7 (2nd March 2017) - Scherr, Thomas F.; Gupta, Sparsh; Wright, David W.; Haselton, Frederick R.
Abstract : Barcode embedded rapid diagnostic tests are presented as a tool for improved communication in malaria elimination campaigns. Abstract : Many countries are shifting their efforts from malaria control to disease elimination. New technologies will be necessary to meet the more stringent demands of elimination campaigns, including improved quality control of malaria diagnostic tests, as well as an improved means for communicating test results among field healthcare workers, test manufacturers, and national ministries of health. In this report, we describe and evaluate an embedded barcode within standard rapid diagnostic tests as one potential solution. This information-augmented diagnostic test operates on the familiar principles of traditional lateral flow assays and simply replaces the control line with a control grid patterned in the shape of a QR (quick response) code. After the test is processed, the QR code appears on both positive or negative tests. In this report we demonstrate how this multipurpose code can be used not only to fulfill the control line role of test validation, but also to embed test manufacturing details, serve as a trigger for image capture, enable registration for image analysis, and correct for lighting effects. An accompanying mobile phone application automatically captures an image of the test when the QR code is recognized, decodes the QR code, performs image processing to determine the concentration of the malarial biomarker histidine-rich protein 2 at the test line, and transmits the test results and QR code payload to a secure web portal. This approach blends automated, sub-nanomolar biomarker detection, with near real-time reporting to provide quality assurance data that will help to achieve malaria elimination.